Cryoprotection effectiveness of low concentrations of natural and lyophilized LDL (low density lipoproteins) on canine spermatozoa - M.M. Neves; L.G.D. Heneine; M. Henry (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2014)
The aim of this study was to evaluate the use of low concentrations of natural and lyophilized low density lipoprotein (LDL) from hen's egg yolk for cryopreservation of canine semen. Different ammonium sulphate concentrations were tested to extract LDL from egg yolk. The yolk was centrifuged, and LDL was isolated using 10, 20, 40, 45, or 50% ammonium sulphate solution (ASS). The LDL-rich floating fraction was collected for chemical characterization. Dry matter content was lowest (P<0.05) in the LDL extracted with the 50% ASS. The purification of LDL increased in association with increasing ammonium sulphate concentrations. SDS-PAGE showed that the 50% ASS solution yielded a purer fraction of LDL from egg yolk. For semen cryopreservation, TRIS extender was used replacing 20% egg yolk (control) by natural or lyophilized LDL using 1, 2, and 3% (w/v). Semen was centrifuged (755Xg for 7 min), diluted with one of the extenders, packed into 0.5mL straws (100x106 sperm/mL), and placed in a programmable cryopreservation machine. Thawed semen (37°C/ 30s) was analyzed for sperm motility, morphology, and by the hypoosmotic and epifluorescence tests (CFDA/ PI). Natural LDL extracted with 50% ASS was as effective as whole egg yolk to preserve canine frozen sperm when using low concentrations. The lyophilized LDL, mainly in the two higher concentrations tested (2 and 3%), was unsuitable to maintain the effectiveness of the LDL cryoprotective effect on dog sperm.